RELATIONSHIP OF CONTROLLED HYPERTENSIVE WITH DEGREE OF HYPERTENSIVE RETINOPATHY ON SPECIAL EYE HOSPITAL IN SOUTH SUMATERA - Fadillah; Sari, Salsabilla Sylvia; Sari, Saputra Edi (Majalah Kedokteran Sriwijaya, 2025)
Hypertension is defined as an increase in systolic blood pressure >140 mmhg and diastolic pressure >90 mmhg. Based on Riskedas’s data 2018, prevalence of hypertension in Indonesia was 34,11%. Patient with uncontrolled blood pressure were at high risk of damage organs such as retina of eye which can cause hypertensive retinopathy. The extent and severity of retinopathy can divided into four degree according to Keith Wagener Barker Classification System. The severity of degree retinopathy hypertensive can be prevented by controlling blood pressure. The purpose of this research was to determine the relationship between blood pressure and degree of hypertensive retinopathy at special eye hospital in south sumatera during 2019-2022. This methods of research is analytical observational using a cross sectional design. From total sampling methods, 21 samples were obtained who met inclusion criteria. The highest people who is suffered uncontrolled blood pressure in grade III hypertensive retinopathy was 9 people (56,3%) and people who had controlled blood pressure in grade I hypertensive retinopathy was 3 people (60.0%) . There is a relationship between controlled blood pressure control and the degree of retinopathy hypertensive at eye’s hospital with p value (0.034%)